2021
DOI: 10.1038/s41467-021-24100-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity-induced nanoparticle circumgyration at sub-diffraction scale

Abstract: The ability of light beams to rotate nano-objects has important applications in optical micromachines and biotechnology. However, due to the diffraction limit, it is challenging to rotate nanoparticles at subwavelength scale. Here, we propose a method to obtain controlled fast orbital rotation (i.e., circumgyration) at deep subwavelength scale, based on the nonlinear optical effect rather than sub-diffraction focusing. We experimentally demonstrate rotation of metallic nanoparticles with orbital radius of 71 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
(49 reference statements)
1
22
0
Order By: Relevance
“…In addition, from data in Figure 5a,b, after plotting the magnitude of the displacement vector at each point against the radius from the center the median values of the radius were calculated by Gaussian fitting to be 39 nm for Figure 5a and 28 nm for Figure 5b, respectively. These values are almost the same as the gap size, and smaller than the minimum radius of 71 nm for nanoscale rotational motion based on the nonlinearity of gold nanoparticles recently reported by Qin et al 46 These results are in good agreement with the simulation results shown in Figure 2a and demonstrate the transfer of angular momentum between the excited, localized plasmonic resonant mode and the motion of the trapped ND. In this study, we demonstrate how to induce and control the nanoscale orbital rotation of a 100 nm ND trapped above a plasmonic nanogap.…”
supporting
confidence: 91%
“…In addition, from data in Figure 5a,b, after plotting the magnitude of the displacement vector at each point against the radius from the center the median values of the radius were calculated by Gaussian fitting to be 39 nm for Figure 5a and 28 nm for Figure 5b, respectively. These values are almost the same as the gap size, and smaller than the minimum radius of 71 nm for nanoscale rotational motion based on the nonlinearity of gold nanoparticles recently reported by Qin et al 46 These results are in good agreement with the simulation results shown in Figure 2a and demonstrate the transfer of angular momentum between the excited, localized plasmonic resonant mode and the motion of the trapped ND. In this study, we demonstrate how to induce and control the nanoscale orbital rotation of a 100 nm ND trapped above a plasmonic nanogap.…”
supporting
confidence: 91%
“…[4] However, a particle trapped at a distance from the beam center is expected to rotate around the beam center (orbital motion) due to the action of the optical torque. [11,12] It was experimentally verified that the orbital motion direction of trapped VO 2 nanoparticles can be controlled by the circular polarization direction of the incident light. When the electric field was rotating in the clockwise (respectively counter-clockwise) direction, the trapped particle was also rotating in the clockwise (respectively counter-clockwise) direction.…”
Section: Polarization-controlled Orbital Rotationmentioning
confidence: 97%
“…This effect has been investigated in previous works using birefringent particles trapped by a CW Gaussian laser beam [11] and gold nanoparticles trapped by a femtosecond laser. [12] However, the phase transition of VO 2 makes it possible to reach orbit diameters larger than the wavelength. By varying the laser power, it is therefore possible to investigate the spatial distribution of the optical force field in the cross-sectional plane of the focused Gaussian beam.…”
Section: Polarization-controlled Orbital Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another experiment, however, showed that the distance between the potential minima was determined by the distribution of the longitude electromagnetic field of the focused beam . Further investigations are still needed with these systems for optical manipulation involving the nonlinearity. ,, Apart from the particle nonlinearity, a particle with linear permittivity locating in the nonlinear surrounding medium can also show the exotic pulling force . Therefore, more efforts considering the degree of freedom of nonlinearity are of necessary for optical manipulation in some physical scenarios.…”
Section: Outlook and Conclusionmentioning
confidence: 99%